2010
DOI: 10.1016/j.ijrobp.2010.07.709
|View full text |Cite
|
Sign up to set email alerts
|

Change in CA 19-9 Levels after Chemoradiotherapy Predicts Survival in Patients with Locally Advanced Unresectable Pancreatic Cancer

Abstract: .Purpose: RTOG 9704 demonstrated a prognostic role for postoperative CA 19-9 in patients with resectable pancreatic carcinoma following surgery. Our study aimed to investigate whether CA 19-9 provided similar prognostic information in patients with locally advanced unresectable pancreatic cancer (LAPC) treated with chemoradiotherapy (CRT) and to determine whether such endpoints should therefore be reported in future randomized trials. Only patients with a bilirubin of less than 2 mg/dL at the time the CA 19-9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…This wide range of accrual is somewhat reflected in various chemotherapy regimens employed. Also, CA 19-9 values, known to be important prognostic factor (23,26), were unavailable for more than one-third of the patients, especially those treated in earlier period, which may have impacted current prognosticator analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This wide range of accrual is somewhat reflected in various chemotherapy regimens employed. Also, CA 19-9 values, known to be important prognostic factor (23,26), were unavailable for more than one-third of the patients, especially those treated in earlier period, which may have impacted current prognosticator analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the contribution of these events to chemotherapy resistance remains to be determined. Adding to these findings, several studies associated elevation of serum sTn antigen (detected by the CA72-4 test) and sLe a (detected by the CA19-9 test) levels in cancer patients with both recurrence after chemotherapy, metastasis and poor overall survival (Kim DH et al, 2015;Yang GY et al, 2013;Ziske C et al, 2003), suggesting that the presence of these glycans may be associated with drug resistance. However, this hypothesis warrants confirmation in future studies.…”
Section: Protein Glycosylation: Contribution To Chemoresistancementioning
confidence: 98%
“…In particular, several reports associate the overexpression of sLe a with decreased overall survival in digestive tract tumors (Kannagi R, 2007;Matsui T et al, 2004;Portela SV et al, 2011). Furthermore, serological detection of sLe a on glycolipids and glycoproteins by the CA19-9 assay is used as a diagnostic tool to monitor clinical response to therapy for these tumors (Humphris JL et al, 2012;Kannagi R, 2007;Yang GY et al, 2013). Furthermore, the 2,6-oversialylation of lactosamine chains and overfucosylation of terminal motifs are also among some of the commonly observed structural alterations present in cancer cells (Christiansen MN et al, 2014).…”
Section: Protein Glycosylation: Structural Diversity In Cancermentioning
confidence: 99%
“…For example, patients with a CA19-9 level greater than 1,000 U/ml at time of diagnosis were more likely to have unresectable disease (40). Biomarker analysis in large phase 3 pancreatic cancer trials showed that a decrease in CA19-9 by at least 90% correlated with increased survival (41)(42)(43). Prognostication studies by Reni et al showed that the basal value of CA19-9 in advanced pancreatic disease correlated with survival (44,45).…”
Section: Ca125mentioning
confidence: 99%